Hungarian Question at the United Nations. Expenses Approved for Sir Leslie Munro - Héderváry, Claire de (1959)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Radio Free Europe Sir Leslie Munro has been voted $15,300 to cover official expenses arising out of his assignment as United Nations Representative on the Question of Hungary. Soviet Bloc representatives objected as it was believed that this is interference in the domestic affairs of Hungary. The votes were cast as follows: 47 in favor, 8 against and 3 abstentions.